PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS WEB TERHADAP HASIL BELAJAR RANAH PSIKOMOTOR SISWA PADA MATA PELAJARAN PEMBUATAN POLA DI SMKN 6 SURABAYA - Luh Wina Sadevi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
The purpose of this study was to determine the effects of using multimedia web-based on learning outcome, especially psychomotor domain of XI Fashion Boutique students in SMKN 6 Surabaya, on the subject study Pattern Making. Quasi-Experimental design has been used, which consists of experimental class (multimedia web-based) and control class (power point), wherein consists of 30 students for each class. Data was analyse using Independent sample t-test on SPSS software. The data showed that psycomotor domain of the experimental class were higher than control class.